Selective Ethanolysis of Fish Oil Catalyzed by Immobilized Lipases - Moreno‐Pérez, Sonia; Guisan, Jose M.; Fernandez‐Lorente, Gloria (Journal of the American Oil Chemists' Society, 2013)
Abstract Selective ethanolysis of fish oil was catalyzed by immobilized lipases and their derivatives in organic media. Lipases from Candida antarctica B (CALB), Thermomyces lanuginosa (TLL) and Rhizomucor miehei (RML) were studied. The three lipases were immobilized by anion exchange and hydrophobic adsorption. The discrimination between the ethyl ester of eicosapentaenoic acid (EE‐EPA) and the ethyl ester of docosahexaenoic acid (EE‐DHA) depends on the lipase, the immobilization support, the physico‐chemical modifications of the immobilized lipase derivatives and on the solvents used. TLL and RML were much more selective than CALB. EE‐EPA is released 20‐fold faster than EE‐DHA when ethanolysis was catalyzed, in cyclohexane, by TLL hydrophobically adsorbed on Sepabeads C18. The selectivity and stability of the different derivatives in these polar organic solvents were further improved after physico‐chemical modification. The best results for activity‐selectivity‐stability were obtained in cyclohexane for TLL adsorbed on Sepabeads C18 and further modified via solid‐phase physical modification with a polyethylenimine polymer. In this case, the initial selectivity was higher than 20, and a 80 % of EPA was released as ethyl ester after 3 h at 25 °C. At this conversion, mixtures of ethyl esters highly enriched in the ethyl ester of EPA with less than 5 % of the EE‐DHA were obtained. TLL derivatives remained fully active after incubation for 24 h in anhydrous solvents.